Love unites the Muslim Ummah across different political backgrounds - Syaidatun Nazirah Abu Zahrin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The power of love can make a great contribution and impact to humanity and the world at large. This article will discuss about love uniting Muslim Ummah (LUMU), and how to apply it among Muslims with different political backgrounds. LUMU is one of the Islamic education agenda to prepare the Muslims in term of knowledge, faith and practical activities in daily life. This conceptual paper will highlight on the importance of love in upholding the sovereignty of the Muslim kings, protection of the beloved land of Malaysia and the well being of the Ummah, through the worldly activities (amal) especially in the empowerment of Muslim political and economic conditions. A library search was executed with the references ranging from the year of 1991 to 2024. This study has been analyzed thematically and several themes have existed, namely love in Islam is a concept that can unite the Ummah; appreciate different political views; preserving the status of the Sultan and King; love for homeland; and LUMU deeds from the perspective of politics, economics and education. It is discovered that love could be the catalyst in uniting the Ummah and strengthen Malaysia as one of prestigious Muslim country recognized around the globe.